Juridical Study On The Competence of Religion Courts In Completing Syariah Banking Disputes Based On Article 55 Law Number 21 of 2008 Concerning Banking Syari'ah - M.Hidayat; Sinarianda Kurnia (Faculty of Law, Merdeka University Surabaya, 2018)
If we want to respect Law No. 3 of 2006 concerning Religious Courts, give full competence in sharia banking disputes to the Religious Courts. Including the issue of mortgages (guarantees, red) and their execution,